The rhetoric of shame in religious and political discourses : constructing the perpetrator in South African academic discourse - Snyman, Gerrie 19XX- (Old Testament essays, 2006)
This paper deals with the rhetoric of shame that constructs the Western intellectual heritage as a cultural perpetrator. It starts with discussing the phenomenon of shame and its waning influence in the West's emphasis on individuality. It then deals with two sets of criticism: those within the pages of The Bible in Africa. Transactions, Trajectories, and Trends (2000) by G O West and M Dube and those in S Kelley's book (2002) Racializing Jesus. Race, ideology and the formation of modern biblical scholarship. The paper then looks at the affect of these rhetorical strategies in terms of honour and shame with the help of J M Coetzee's novel (2000), Disgrace. Lastly, the paper looks for pointers in Krondorfer's book, Remembrance and Reconciliation: Encounters between young Jews and Germans (1995), to deal with disgrace or shame.